Characteristics of convalescent plasma donors for Covid-19: Barriers for consent - Shafaghi, Shadi; Fazlzadeh, Aylar; Rezaei Asmaroud, Sara; Nasiri, Shamsi; Naghashzadeh, Farah; Keshmiri, Mohammad Sadegh; Noorali, Sima (Researcher Bulletin of Medical Sciences, 2023)
Background and Objective: Covid-19 pandemic is a worldwide bothersome issue. Although the appropriate strategy for plasma donation from recovered Covid-19 cases should be based on clinical, laboratory, and demographic characteristics of cases, consent for plasma donation is crucial. Moreover, the safety of donation is important not only for receiving cases but also for donor subjects. Accordingly in this study, the existing conditions in plasma donors for Covid-19 were assessed. Materials and Methods: In this descriptive cross-sectional study, 264 consecutive cases with positive Covid-19 infection history were enrolled in 2020 a total of 64 cases were eligible for plasma donation. The initial two stages for consent and medical history were done by phone call and two final steps including laboratory results and physical examination were carried out after patients’ attendance to the hospital. Results: Mean (standard deviation) age was 45.3 (9.1) years. There were 58 male cases (90.6%). Totally 70.3% had academic literacy and 90.6% were married. Even thirteen cases (20.3%) had underlying diseases. There was not any significant early or late complication during donation. Causes for plasma donation were mentioned help to humankind, severe disease experience, and help to research projects in 41 (64.1%), 14 (21.8%), and 9 (14.1%) cases, respectively. Conclusions: It is necessary to inform the post-covid-19 patient about the advantages of plasma donation as a safe way for critically ill patients to decrease the burden of the disease in their current condition without confirmed drugs.